Fractal dimension and lacunarity of tractography images of the human brain. (September 2016) - Provata, A.; Katsaloulis, P.; Hizanidi, J.; Verganelakis, D.A.
Abstract : Introduction: Diffusion Tensor Imaging (DTI) is a novel technique that mirrors the complex architecture of the neuron axons fiber networks in the human brain. Purpose: The aim of this work is to measure the structural complexity of brain neurons' using 2 dimensional tractography DTI images and compare the complexity of the textures originating from healthy brain neurons. Materials and methods: Two-dimensional diffusion tensor images from a group of healthy subjects were studied. The generated neuronal tracts by various ROIs on the DTI maps were processed using the Box Counting method and measure self-similarity. The Hausdorff fractal dimension Df was then calculated. Lacunarity studies were also performed in order to describe the complex interconnectivity of neurons. Results: Average fractal dimensions were calculated based on the current resolution of the 2D images for different observational angles. High lacunarity derived values indicate the interconnection in the neurons' distribution as well as clustering and connectivity of the neuron imaged ensemble. Conclusion: The results of this study demonstrate firstly that, the average estimated fractal dimension of tractography images for healthy subjects is Df = 1.60 and secondly statistical self-similarity features.